Prehistoric „cooperative families“: Neolithic households between tradition and innovation - Boban Tripković (University of Belgrade, 2016)
The beginning of production, private property and the division of labor are often distinguished as the socio-economic context for the earliest emergence of cooperative families. In this paper the phenomenon of large cooperative families in the neolithic is considered, as the neolithic is the start of production (the domestication of plants and animals) with implications of wider social significance. This paper indicates that a) large neolithic households are based and function according to economic principles, and, most propbably, kinship; b) the neolithic house is an ideological and spatial framework for the display of the identity of cooperating kinship groups; c) the structure, developmental dynamics and interrelations are reflected in the material sphere of the household. Ultimately attention is drawn to the existence of large (family?) households during the neolithic, and that it represents one of the more meaningful phenomena in a time which is otherwise, technologically and materially, suitable for the first clear physical expression of this phenomenon. Because of this, a certain dilemma remains as to whether the beginning of organizing in „cooperative families“ can really be a neolithic innovation (or a consequence of the start of production) or, as this research suggest, the beginnings and the manifestation of this process ought to be sought anew in different periods of the past in varying demographic, cultural and economic circumstances.